User's priority focused resource provisioning over cloud computing infrastructure. (2017) - Madhumathi, R.; Radhakrishnan, R.
Resource provisioning is the process of activating a bundle of allocated quantity of resources to bear the user requests. The scheduling algorithm plays a vital role in effective utilisation of resources, though resource allocation fails to achieve user satisfaction. To overcome this failure, Drip Irrigation-based Resource Allocation (DRA) scheduling algorithm is proposed to exploit the user priority on the basis of the reputation of the users who frequently request the resources. This algorithm works in three stages, namely resource selection, resource matching and drip-based resource allocation, where the unallocated requests are divided into smaller sub-tasks and limited available resources are allocated to them. Simulation results demonstrate that the drip-based resource scheduling mechanism is effective in satisfying the users' diverse requirements by considering their priority. Compared to the First Come First Serve (FCFS) and UFeed algorithms this performs better in terms of resource utilisation rate and satisfies more users in the cloud system.